2019
DOI: 10.1101/773937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental decomposition of cuticular hydrocarbons generates a volatile pheromone that guides insect social behavior

Abstract: 28Once emitted, semiochemicals are exposed to reactive environmental factors that may alter them, 29 thus disrupting chemical communication. Some species, however, might have adapted to detect 30 environmentally mediated breakdown products of their natural chemicals as semiochemicals. We 31 demonstrate that air, water vapor, and ultraviolet (UV) radiation break down unsaturated cuticular 32 hydrocarbons (CHCs) of Periplaneta americana (American cockroach), resulting in the emission of 33 volatile organic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Photo-oxidation of CHCs has also been implicated in the formation of volatile semiochemicals in a variety of other insect taxa including Macrocentrus grandii (103), Anoplophora glabripennis (112), and Drosophila melanogaster (71). Recently, Hatano et al (59) demonstrated that nymphs of the American cockroach, P. americana, avoided shelters exposed to volatiles originating from the breakdown of CHCs. In particular, exposing CHCs to ultraviolet radiation resulted in the release of 14 compounds detectable by the cockroach antennae, and a blend of 10 of them elicited avoidance behavior, suggesting that they serve as necromones (signals of death) or epideictic (spacing) pheromones.…”
Section: Influence Of Environment and Diet On Cuticular Hydrocarbon P...mentioning
confidence: 99%
“…Photo-oxidation of CHCs has also been implicated in the formation of volatile semiochemicals in a variety of other insect taxa including Macrocentrus grandii (103), Anoplophora glabripennis (112), and Drosophila melanogaster (71). Recently, Hatano et al (59) demonstrated that nymphs of the American cockroach, P. americana, avoided shelters exposed to volatiles originating from the breakdown of CHCs. In particular, exposing CHCs to ultraviolet radiation resulted in the release of 14 compounds detectable by the cockroach antennae, and a blend of 10 of them elicited avoidance behavior, suggesting that they serve as necromones (signals of death) or epideictic (spacing) pheromones.…”
Section: Influence Of Environment and Diet On Cuticular Hydrocarbon P...mentioning
confidence: 99%
“…CHCs are species-specific and serve multiple functions. The primary role of CHCs is protecting the insects from environmental stress and also evolved secondary functions as chemical signals (Hatano et al, 2019;Pardy et al, 2019). n-alkanes are majorly involved in desiccation resistance increasing the chain length strengthens van der Waals forces with high melting points leads to stability.…”
mentioning
confidence: 99%